The needs of students with disabilities for academic success at the University of Limpopo : a humanistic perspective - Moleke, H.; Montle, M. E.; Mogoboya, M. J. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
The year 2017 marked a vexing protest at the University of Limpopo by Students with Disabilities. Amongst the issues that inspired the protest were contextual factors such as scarcity of resources appropriate for students with special educational needs and inaccessibility of buildings for such students. These are pivotal barriers to the academic success of Students with Disabilities hence the uprisings. Though many South African universities stipulate commitment to this constitutional right, little is practically done to improve the inadequate existing support services rendered to Students with Disabilities in these universities. There is a gaping gap which must be bridged with speed between policies on inclusive education and their implementation. This paper seeks to investigate the needs of Students with Disabilities for academic success in South African universities by using the University of Limpopo' BA Languages undergraduate students as a microcosm of such institutions. This study is grounded on a Humanism theory of education. A phenomenologically designed qualitative research approach was adopted in this study. Data, which was purposively sampled, was collected through interviewing undergraduate BA Languages Students with Disabilities in their residences at the university. This data was analysed by using a thematic content analysis (TCA) technique. The pressing needs of Students with Disabilities were identified, analysed and discussed, and proactive recommendations provided. The results of the paper indicated that academic success of Students with Disabilities relies heavily on addressing their basic special needs. Keywords: Constitutional rights, Inclusive education, humanism, Special needs, Support services
Journal article published in The International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Constitutional rights; Inclusive education; Humanism; Special needs; Support services; Inclusive education -- South Africa; Children with disabilities